THE PLACE AND ROLE OF KYRGYZSTAN IN THE DEVELOPMENT OF THE EURASIAN ECONOMIC UNION - V. V. Perskaya (Финансы: теория и практика, 2017)
The paper analyzes the place and role of the economy of Kyrgyzstan in the Eurasian Economic Union; discusses geo-economic and political vectors of foreign interests in Central Asia aiming exclusively at own ambitions and political preferences. It reveals the importance of Kyrgyzstan’s participation in the Eurasian Economic Union based on the preservation of national statehood and sovereignty in the domestic and foreign policy and the synchronized government regulation of the investment and business environment within the Eurasian Economic Union.In pursuing its national interests, Kyrgyzstan is trying to carry out a targeted balanced multi-vector foreign policy. At the same time Kyrgyzstan’s foreign policy activities commensurate with its own potential and involvement in the world process. Viewed from the above, the following main goals of the modern foreign policy are put forward: strengthening the independence and sovereignty, ensuring the security and territorial integrity of the country, carrying out democratic transformations,strengthening the foundations of the constitutional order,protection of human rights and freedoms, creating favorable external conditions for a sustainable internal development,formation of a good neighborliness belt on the perimeter of the country borders, establishment and enhancement of the investment climate in the Republic.